The multifaceted roles of natural products in mitochondrial dysfunction - Chen, Qianrun; Ruan, Danhua; Shi, Jiayan; Du, Dongru; Bian, Ce (Frontiers in Pharmacology, 2023)
Mitochondria are the primary source of energy production in cells, supporting the metabolic demand of tissue. The dysfunctional mitochondria are implicated in various diseases ranging from neurodegeneration to cancer. Therefore, regulating dysfunctional mitochondria offers a new therapeutic opportunity for diseases with mitochondrial dysfunction. Natural products are pleiotropic and readily obtainable sources of therapeutic agents, which have broad prospects in new drug discovery. Recently, many mitochondria-targeting natural products have been extensively studied and have shown promising pharmacological activity in regulating mitochondrial dysfunction. Hence, we summarize recent advances of natural products in targeting mitochondria and regulating mitochondrial dysfunction in this review. We discuss natural products in terms of their mechanisms on mitochondrial dysfunction, including modulating mitochondrial quality control system and regulating mitochondrial functions. In addition, we describe the future perspective and challenges in the development of mitochondria-targeting natural products, emphasizing the potential value of natural products in mitochondrial dysfunction.